Peningkatan Kebahagiaan di Tempat Kerja : Penggunaan Website Tiga Hal Baik pada Pelatihan Kebersyukuran - Nur Rahmat Laba; Erika Setyanti Kusumaputri (JIP (Jurnal Intervensi Psikologi), 2020)
This study aims to determine the effectiveness of gratitude exercise using three good things techniques on happiness at work enhancement. Participants of this study were 15 employees aged 21-28 years divided into two groups: eight participants in the experimental group and seven participants in the control group. The design was a randomized two-group pretest-posttest. Collecting data used to happiness at work scale with Likert model prepared by the researcher. Data analysis methods used by using Mann Whitney U technique for differences of the gain score in the experimental group and control group data score. The result of gain score analysis showed t value = 8.500 and p-value of 0.021 (p<0.05), indicating there is a significant difference between the experimental group and control group after gratitude exercise. The result shows that gratitude exercise using three good things techniques is effective to increase happiness at work of employees. Key notes: gratitude exercise, happiness at work, three good things